2014
DOI: 10.1017/s1751731114001347
|View full text |Cite
|
Sign up to set email alerts
|

Non-genetic sources of variation of milk production and reproduction and interactions between both classes of traits in Sicilo-Sarde dairy sheep

Abstract: This work aimed to study the sources of variation in productive and reproductive traits of the dairy Sicilo-Sarde ewes and to further investigate the interaction between both classes of traits. After edits, a database containing 5935 lactation records collected during 6 successive years in eight dairy flocks in the North of Tunisia was used. Total milked milk (TMM) in the milking-only period was retained as productive trait. The interval from the start of the mating period to the subsequent lambing (IML) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…(Selmi et al, 2009). Par ailleurs, une caractérisation préliminaire de la relation entre la production laitière et la reproduction des brebis sicilo-sardes (Aloulou et al, 2011), confortée par les travaux de Meraï et al (2014), a permis de confirmer l'antagonisme de ces deux caractères chez les ruminants laitiers (Bodin et al, 1999). Il faudra donc être attentif à ne pas détériorer les performances de reproduction lorsqu'on cherchera à améliorer la productivité laitière.…”
Section: Conduites D'élevageunclassified
“…(Selmi et al, 2009). Par ailleurs, une caractérisation préliminaire de la relation entre la production laitière et la reproduction des brebis sicilo-sardes (Aloulou et al, 2011), confortée par les travaux de Meraï et al (2014), a permis de confirmer l'antagonisme de ces deux caractères chez les ruminants laitiers (Bodin et al, 1999). Il faudra donc être attentif à ne pas détériorer les performances de reproduction lorsqu'on cherchera à améliorer la productivité laitière.…”
Section: Conduites D'élevageunclassified
“…A recent study taken in the Sicilo-Sarde breed [80] showed an average of daily milk production of 0.46 L with a high variation between 0.10 and 2.40 L and a milk period of 132.8 days. This study shows also a similar milking-only length (139 ± 47 days) and suckling length (104 ± 22 days) to previous reports [81].…”
Section: Review On the Milk Potentialities Of Goats And Sheep Raised mentioning
confidence: 93%
“…Many studies analyzing the factors affecting ewes' growth performance, milk yield and milk composition were reported (Al-Barzinji and Hassan, 2005; Antonič et al, 2013). The main factors were flock (Meraï et al, 2014;Everett-Hincks, et al, 2014;Rahimi et al, 2014), ewes age (Ramakrishanappa et al, 2015;Sezenler et al, 2016;Siddalingamurthy et al, 2017)…”
Section: Introductionmentioning
confidence: 99%